there is no solution (option D)
Step-by-step explanation:
x + y = -4 ...equation 1
-2x - 2y = 6 ...equation 2
using elimination method:
let's eliminate y. Multiply equation 1 by 2 so the coefficient of y are the same:
2x + 2y = -8 ...equation 1
-2x - 2y = 6 ...equation 2
Add equation 1 and 2:
2x + (-2x) + 2y + (- 2y) = -8 + 6
Multiplication of same sign gives positive number. Multiplication of opposite signs give negative number.
2x - 2x + 2y - 2y = -2
0 + 0 = -2
0 = -2
left side not equal to right side of the equation
When the left hand side of the equation has a different number from the right hand side of the equation, we say there is no solution (option D)